The effect of oil heat treatment on the color and the community’s color preferences of two Gigantochloa species - Permana, Anom Tahta; Suri, Intan Fajar; Febryano, Indra Gumay; Hidayat, Wahyu (Global Forest Journal, 2025)
friendly material. Two local Indonesian bamboo species, namely apus bamboo(Gigantochloa apus) and ater bamboo (Gigantochloa atter), have been widelyused in various fields but still face challenges such as fading color and lowresistance to moisture. This study aims to investigate the color changes in apusbamboo and ater bamboo after undergoing heat treatment using oil at varyingtemperatures of 160°C, 180°C, 200°C, and 220°C. Five-year-old bamboo sampleswere cut into cylindrical shapes with a diameter of 10 cm and a height of 5 cm,then tested for color before and after the heat treatment. The treatment was carriedout for 2 hours using oil as a medium, then dried in an oven. Color changes wereanalyzed using a general colorimeter scanner. Data collection on communitypreferences for bamboo colors was conducted by distributing questionnaires. Thered-green chromaticity changes in apus bamboo exhibit a decreasing trend,whereas ater bamboo shows an increasing trend. The yellow-blue chromaticitychanges in both bamboo species show an increasing trend. For the lightness level,both bamboos have decreased. The overall color change in apus bamboo and aterbamboo increases with the increasing temperature. The color preference resultsrevealed that women prefer bright colors in both bamboo species. Men are moreselective in their color preferences; some choose bright colors, but many alsochoose dark colors.